Safety Profile of Caesalpinia spinosa Aqueous Extract Tested in Oreochromis niloticus Toward Its Application in Dermocosmetics - Salirrosas, David; Reategui-Pinedo, Nataly; Crespo, Jan Pier; Sánchez-Tuesta, Linda; Arqueros, Mónica; Cabrera, Angelita; Martinez, Renata Miliani; Ayala, Carmen; Baby, André Rolim; Prieto, Zulita Adriana (Frontiers in Sustainability, 2021)
Herbal extracts have been widely used in dermocosmetics as a source of biomolecules and, also, as a natural claims. Fruits from Caesalpinia spinosa show great potential for their polyphenolic content, preservative and film forming features, as previously reported in specialized literature, however, the toxicity requires investigation. We explored Oreochromis niloticus (tilapia) in larval, alevins and juvenile stages to evaluate the ex vivo and in vivo genotoxicity and in vivo acute and chronic toxicity of C. spinosa aqueous extract in different concentrations. Citotoxicity, animal behavior, morphological deformities and DNA damage were evaluated. Our results showed genotoxic effect in ex vivo tests, but no DNA damage in in vivo erythrocytes. We suggest a mechanism of cell permeability involved in the toxicity of C. spinosa aqueous extract. Internal validation showed the feasibility of O. niloticus applied for toxicity evaluation. Further studies could contribute for better understanding the uses and safety of C. spinosa in cosmetics and topical pharmaceutical products.